Uso da metodologia emergética para avaliação da sustentabilidade de agroecossistemas de produção de grãos - Pauletti, Elisson Stephânio Savi (2016)
The sustainability is guided in the difficult balance between food production and the preservation of natural resources, with agriculture one of the strategic areas in pursuing this goal. Grain production systems require large amounts of energy and resources in its production process. Soybeans, corn and beans are the most grain crops grown in Brazil, totaling nearly 50 million hectares. The emergy methodology presents a proposal for evaluation of sustainability for production systems from emergy. It is an energy approach, based on thermodynamic and ecology systems which have been used in many countries of the world. The objective of this study was to evaluate the sustainability of soybean production systems, corn and beans in tillage and conventional tillage, through the emergy methodology, from data collected in a field experiment. The experiment was conducted during the seasons of 2013/14, 2014/15 and 2015/16. The experimental design was a randomized complete block design with three treatments and four replications. The treatments were the production systems with different crop rotation arrangements: T1 (system 1/tillage: oatmeal+turnip/beans - oats/corn - oats+vetch/corn), T2 (system 2/tillage: oats+vetch/soybeans - vetch/corn - oat+radish/soybean) and T3 (3 system/conventional tillage: winter fallow and beans, corn and soybeans in the summer). The emergy analysis followed the three basic methodological steps proposed by Odum (1996): (1) elaboration of the ecosystem diagram; (2) construction of tables for the calculation of the total emerging and, (3) discussion of emergy indicators obtained. Classic emergy indicators were used: total emergy system (Y), system transformity (TR), emergy yield rate (EYR), renewability (R%), emergy investment rate (EIR), environmental load (ELR) and emergy sustainability index (ESI). The results obtained were: ESI, 2,26 - 2,93 - 1,17 and R% 50,62% - 54,83% - 34,43% for T1, T2 and T3, respectively. The use of emergy methodology for assessing the sustainability of grain production systems, based on this study, proved to be consistent and appropriate. It was concluded that the systems managed in tillage, crop rotation and winter cover, (T1 and T2), showed the best environmental and economic indicators and the best energy responses (ratio emerged spend and energy produced), and sustainable in medium and long term and that the managed system in conventional tillage with winter fallow (T3) is unsustainable in the long term.